The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.neo.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Copy Number Amplification and Hyperactivating Somatic Mutations of EZH2 Correlate With DNA Methylation and Drive Epigenetic Silencing of Genes Involved in Tumor Suppression and Immune Responses in Melanoma

Abstract: The epigenetic modifier EZH2 is in the center of a repressive complex controlling differentiation of normal cells. In cancer EZH2 has been implicated in silencing tumor suppressor genes. Its role in melanoma as well as target genes affected by EZH2 are poorly understood. In view of this we have used an integrated systems biology approach to analyze 471 cases of skin cutaneous melanoma (SKCM) in The Cancer Genome Atlas (TCGA) for mutations and amplifications of EZH2. Identified changes in target genes were vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 33 publications
(56 reference statements)
0
51
0
1
Order By: Relevance
“…Melanoma is the most frequently EZH2-mutated solid neoplasm [37]. Melanoma cells harbor the Y641 activating mutation within the catalytic SET domain that was first described in Diffuse large B-cell (DLBC) lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is the most frequently EZH2-mutated solid neoplasm [37]. Melanoma cells harbor the Y641 activating mutation within the catalytic SET domain that was first described in Diffuse large B-cell (DLBC) lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer care, phenotype-driven gene target definition is typical and clinical genome-wide sequencing data interpretation is still accompanied by a large-scale research effort [84]. Here, we illustrate a complete precision medicine profile of a malignant melanoma patient [85] (Figs. 3 and 4).…”
Section: Precision Medicine Profile Of Malignant Melanoma Patient Witmentioning
confidence: 99%
“…The study on efficient detection of genomic drivers in malignant melanoma identified co-occurrence of a mutational and copy number hotspot on chromosome 7 including the known BRAF locus [13]. Interestingly, the activating somatic BRAF(V600E) mutation is accompanied by somatic mutation and/or somatic copy number amplification of prominent epigenetic regulators such as enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2, KMT6A, Gene ID: 2146), lysine demethylase 7A (KDM7A, JHDM1D, Gene ID: 80853), and euchromatic histone lysine methyltransferase 2 (EHMT2, KMT1C, Gene ID: 10919) [13, 85]. The detailed analysis of the mutational landscape of BRAF revealed missense mutations in the ATP-binding site of G466, S467, and G489 as well as in the activator loop of D594, L597, and K601 in the proximity of residue V600 [13].…”
Section: Precision Medicine Profile Of Malignant Melanoma Patient Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Выявлены также эпигенетические предикторы. Амплификации и активирующие соматические мутации в гене EZH2 кор-релируют с уровнем метилирования ДНК, обеспечивая эпигенетическую инактивацию ряда генов, вовлеченных в опухолевую супрессию, и иммунный ответ при меланоме (Tiffen et al, 2016).…”
Section: системная биология и биомедицинаunclassified